Cheating in the Lab Predicts Fraud in the Field: An Experiment in Public Transportations - Zhixin Dai; Fabio Galeotti; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2016)
We conduct an artefactual field experiment using a diversified sample of passengers of public transportations to study attitudes towards dishonesty. We find that the diversity of behavior in terms of dis/honesty in laboratory tasks and in the field correlate. Moreover, individuals who have just been fined in the field behave more honestly in the lab than the other fare-dodgers, except when context is introduced. Overall, we show that simple tests of dishonesty in the lab can predict moral firmness in life, although frauders who care about social image cheat less when behavior can be verified ex post by the experimenter.
Keywords: B41; C91; C93; K42; 330; dishonesty; fare-dodging; field experiment; external validity; public transportations